Sarcomas not rhabdomyomata of soft parts. Presentation of a case. - Julio Sarmiento Sánchez; Dorys González Díaz; Lidia Torres Aja (Medisur)
We present the case of a 20 year-old patient, black race, that ,when going to the Hospital "Princess Marina" in Botswana, February 2nd, 2003, reported to have had, for 5 years, a ball in the internal face of the left arm that had grown slow and progressively. The physical exam, in the moment of admission presented a giant tumour in the internal face of the left arm, of hard consistency, stuck to the skin and with necrosis areas and fetid exudates, but without adherence to deep levels. When carrying out the surgical intervention, the anato- pathological report informed that it was a sarcoma not rhabdomyomata of soft parts.